Paroxysmal Explosions, Lava Fountains and Ash Plumes at Etna Volcano: Eruptive Processes and Hazard Implications - Calvari, Sonia; Cannavò, Flavio; Bonaccorso, Alessandro; Spampinato, Letizia; Pellegrino, Alessandra G. (Frontiers in Earth Science, 2018)
Lava fountains have a major impact on the local population since they cause ash plumes that spread several kilometers above and hundreds of kilometers away from the crater. Ash fallout is responsible for disrupting airports and traffic on the motorways well beyond the area of the volcano itself, as well as affecting the stability of buildings and causing public health issues. It is thus a primary scientific target to forecast the impact of this activity on local communities on the basis of parameters recorded by the monitoring network. Between 2011 and 2015, 49 paroxysmal explosive episodes occurred at two of Mt Etna's five summit craters: the New South-East Crater (NSEC) and the Voragine (VOR). In this paper, we examine the features of the 40 episodes occurring at the NSEC during 2011–2013, and of the 4 events at VOR in December 2015. We study these paroxysms using geophysical monitoring data, characterize the episodes, and analyse all available data statistically. Our main results are two empirical relationships allowing us to forecast the maximum elevation of the ash plume from the average height of the lava fountain, useful for hazard assessment and risk mitigation. For Etna, and using the examples described in this paper, we can infer that wind speed <10 m s−1 generally results in strong to intermediate plumes rising vertically above the crater, whereas wind speed >10 m s−1 is normally associated with weak plumes, bent-over along the wind direction and reaching lower elevations.